A novel, minimally invasive approach to assure hemostasis for intercostal bleeding after trauma. Issue 6 (June 2018) - Park, Habeeba; Glaser, Jacob; Florecki, Katherine; Schmoekel, Nathan; DuBose, Joseph; Stein, Deborah; Scalea, Thomas
Abstract : ABSTRACT: Intercostal artery injury can cause large hemothoraces. While many patients with intercostal artery injury present hemodynamically unstable and require emergent thoracotomy for hemostasis, some tamponade spontaneously. They may rebleed later, however, and cause recurrent hemothorax or retained hemothorax. Video-assisted thoracic surgery (VATS) is an effective way to evacuate retained hemothorax. However, assessing and ligating intercostal artery injury during VATS can be difficult, and often, open thoracotomy is pursued. Even with open surgery, ligation of the intercostal artery can be a challenge. We present a minimally invasive method of definitive intercostal artery ligation during VATS or open thoracotomy.